Hospitality and Travel Marketing / Third Edition - Morrison Alastair M (Delmar Thomson Learning, 2002)
This volume expresses the relationship between marketing and the tourism industry, and emphasizes a broader marketing perspective through collaborative efforts between hotels, airlines, restaurants, and travel agencies. Introduction to Marketing, Marketing Defined, Marketing Hospitality and Travel Services, The Hospitality and Travel Marketing System, Research and Analysis, Customer Behavior, Analyzing Marketing Opportunities, Marketing Research, Planning: Marketing Strategy and Planning, Marketing Strategy: Market Segmentation and Trends, Marketing Strategy: Strategies and Positioning and Marketing Objectives, The Marketing Plan and the 8 Ps, Implementing the Marketing Plan, Product Development and Partnership, People: Services and Service Quality, Packaging and Programming, The Distribution Mix and the Travel Trade, Communications and the Promotional Mix, Advertising, Sales Promotion and Merchandising, Personal Selling and Sales Management, Public Relations and Publicity, Pricing, Controlling and Evaluating the Plan, Marketing Management and Evaluation and Control, Appendices, Glossary, Index.